Relationship among genetic polymorphism of SLCO1B1, rifampicin exposure and clinical outcomes in patients with active pulmonary tuberculosis. Issue 9 (5th March 2021) - Kim, Eun Sun; Kwon, Byoung Soo; Park, Jong Sun; Chung, Jae‐Yong; Seo, Soo Hyun; Park, Kyoung Un; Song, Junghan; Yoon, Seonghae; Lee, Jae Ho
Abstract : Aims: Rifampicin is a key drug for the treatment of tuberculosis (TB). Little is known for the relationship between the rifampicin pharmacokinetics and genetic polymorphisms in the Asian population. We aimed to investigate relationship between genetic polymorphism of SLCO1B1 and rifampicin exposure and its impact on clinical outcomes in Korean patients with active pulmonary TB. Methods: From February 2016 to December 2019, patients with active pulmonary TB who were taking rifampicin for >1 week were prospectively enrolled. Serial or 1‐time blood sampling was conducted to determine rifampicin concentrations. The genotype of 4 single nucleotide polymorphisms of SLCO1B1 was determined. To estimate the drug clearance and exposure, population pharmacokinetics analysis was conducted. Clinical outcomes such as time to acid‐fast bacteria culture conversion, chest radiograph score changes from baseline, and all‐cause mortality were also evaluated. The exposure among different SLCO1B1 genotype was compared and relationship between drug exposure and clinical outcomes were explored. Results: A total of 105 patients (70 males and 35 females) were included in the final analysis. The mean age of patients was 55.4 years. The mean drug clearance and exposure were 13.6 L/h and 57.9 mg h/L, respectively. The genetic polymorphisms of SLCO1B1 were not related to rifampicin clearance or exposure. As the rifampicin exposure increased, the chest radiographs improved significantly, but the duration of acid‐fast bacteria culture conversion was not related to the drug exposure. Conclusion: SLCO1B1 gene polymorphisms did not influence rifampicin concentrations and clinical outcomes in Korean patients with active pulmonary TB.